Grazing during the grassland greenup period promotes plant species richness in alpine grassland in winter pastures - Wei, Wanrong; Zhen, Qiaoyan; Deng, Jia; Yue, Hanlin; Qin, Mingsen; Oosthuizen, Maria K. (Frontiers in Plant Science, 2022)
Although grazing is the most common use of grassland, the ecological function of grassland far exceeds its productivity. Therefore, the protection of plant diversity is of utmost importance and cannot be ignored. Existing research on the effect of grazing on grassland mainly focuses on grazing intensity and the type of livestock, but the effect of the timing of the grazing on the vegetation community is still requires further investigation. We investigated the plant community characteristics of winter pastures in alpine meadow with different grazing termination times (grazing before and during the grassland greenup periods) in Maqu County, eastern Qinghai-Tibet Plateau. The results showed that compared to termination of grazing before the grassland greenup, the extension of grazing into the grassland greenup period of winter pastures significantly decreased vegetation height, coverage, above-ground biomass and Graminoid biomass (P < 0.05). However, grazing during the grassland greenup period significantly increased the total plant species richness and forbs richness (P < 0.05). The structural equation modeling revealed a potential indirect effect on the total plant species richness and forbs richness of winter pastures mainly by a decrease the vegetation coverage and grass biomass abundance. Our findings imply that grazing during the grassland greenup period may facilitate to the maintenance of plant diversity in winter pastures. These findings have important grassland ecological function implications for the conservation of plant diversity at the family ranch scale to a certain extent.cale.